Pengaruh Automatic Teller Machine Dan Mobile Banking Terhadap Kepuasan Nasabah: Studi Kasus Bank Rakyat Indonesia Cabang Baranangsiang Kota Bogor - Agustin, Audilia; Rosa, Edy Safni; mulyana, ade (Jurnal Informatika Kesatuan, 2023)
This research is motivated by the rapid internet users. This is due to the increasing needs of the community. One of the people's needs for internet users is the need for bank facilities that can facilitate people in transacting. With good quality bank facilities can affect customer satisfaction. The purpose of this study was to determine (1) the effect of the Automatic Teller Machine (ATM) on customer satisfaction at Bank BRI Baranangsiang Branch, Bogor City. (2) The influence of Mobile Banking on customer satisfaction at Bank BRI Baranangsiang Branch, Bogor City. (3) The effect of Automatic Teller Machine (ATM) and Mobile Banking services on customer satisfaction at Bank BRI Baranangsiang Branch, Bogor City. The purpose of this research is to examine the significant effect of Automatic Teller Machine and Mobile Banking on Customer Satisfaction at Bank BRI Baranangsiang Branch, Bogor City, partially (individually) or simultaneously (together). The result of this study shows that partially Mobile Banking had positive and significant effect on customer statisfaction. Automatic Teller Machine (ATM) have a positive and significant effect on customer statisfaction. And simultaneously Mobile Banking and Automatic Teller Machine (ATM) have a positive and significant effect on customer statisfaction.The number of respondents in this study amounted to 100 respondents. The data in this study were collected using IBM SPSS Statistics 25. This study used a quantitative approach. Sampling by simple random sampling method. The data used are primary data obtained from the results of filling out the questionnaire. The data collection technique used is a questionnaire. In this study using multiple linear regression analysis method by fulfilling the classical assumption test. The results showed Keyword : Automatic Teller Machine, Mobile Banking and Costumer Satisfaction